Adjustment of global imbalances: Illustrative scenarios for Hungary - Cecília Hornok; Zoltán M. Jakab; Máté Barnabás Tóth (Magyar Nemzeti Bank, 2007)
In this study we examine the impact on Hungary of a possible correction of global imbalances. We distinguished four different channels of the global adjustment process, which are widely referred to in the literature (fiscal tightening in the U.S.; housing price correction in the US; an increase in the risk premium of dollar assets; increase in domestic demand in the Asian region) and analyzed them through model simulations. We constructed global scenarios using the NIGEM model, while we captured the domestic impacts using the Quarterly Projection Model (NEM) of the Magyar Nemzeti Bank. According to our results, both the global and domestic effects differ significantly with respect to whether the correction originates from the U.S. or Asia and whether it is a result of policy or market processes. We found that a possible global correction will pass through to Hungary mainly through the Eurozone countries, thus its main impact will be relatively dampened. The responses of domestic macroeconomic variables depend on our assumptions on the reaction of monetary policy and the developments in the risk premium on forint denominated assets.
Keywords: E27; E50; F32; F42; F47; 330; monetary policy; global inbalalnces; forecasting; simulation; Internationale Wirtschaft; Wirtschaftliche Instabilität; Wirtschaftliche Anpassung; Wirtschaftspolitik; Geldpolitik; Szenariotechnik; Wirkungsanalyse; Ungarn